A study of clinical profile, etiology, and echocardiographic parameters in atrial fibrillation at a tertiary care hospital - Abdul Mateen Athar; Kothi Zuber Suleman; Deepak Davis; G Ayesha Siddiqua Begum (Wolters Kluwer Medknow Publications, 2022)
Background: Atrial fibrillation (AF) being the most common arrhythmia encountered clinically is associated with increased mortality and morbidity. Hence, this study was conducted to find the clinical profile, etiology, and echocardiographic factors of AF for the secondary prevention of known complications.Materials and Methods: This was an observational hospital-based study done on 60 patients with AF in the Department of Medicine, St. John's Medical College Hospital, Bengaluru, India. Results: Out of 60 patients with AF, the mean age was found to be 63 years in our study. Female sex (61.67%) had more preponderance to AF than male sex (38.33%). The most common presenting complaint was breathlessness (50%), followed by asymptomatic (25%) and palpitations (21.6%). Surprisingly, a significant number of patients were asymptomatic (25%) during the episode of AF. Hypertension (58.3%) was found to be more prevalent than rheumatic heart disease (RHD) (31.6%) in our patients, the most common complications were noted as heart failure (45%) rather than cerebrovascular accident (CVA) (15%). Nonvalvular AF (68.33%) exceeded the number of patients with valvular AF (31.66%). Ten percent of our subjects had dilated left atrium and 30% of our subjects had ejection fraction of <50%. The most common valvular lesion was found to be mitral regurgitation (45%) followed by mitral stenosis (28.3%). Conclusion: This study has provided insight into the changes in trends pertaining to the clinical profile of AF. The most common predisposing condition is hypertension rather than RHD. Although the most common presenting complaint was breathlessness, there was a significant subset of individuals who were asymptomatic during the AF episode. A significant number of individuals had heart failure and CVA as complications of AF.